UNIT 12C.5 Molecular Typing of Borrelia burgdorferi. Issue 1 (1st August 2014) - Wang, Guiqing; Liveris, Dionysios; Mukherjee, Priyanka; Jungnick, Sabrina; Margos, Gabriele; Schwartz, Ira
Abstract: Borrelia burgdorferi sensu lato is a group of spirochetes belonging to the genus Borrelia in the family of Spirochaetaceae. The spirochete is transmitted between reservoirs and hosts by ticks of the family Ixodidae. Infection with B. burgdorferi in humans causes Lyme disease or Lyme borreliosis. Currently, 20 Lyme disease‐associated Borrelia species and more than 20 relapsing fever‐associated Borrelia species have been described. Identification and differentiation of different Borrelia species and strains is largely dependent on analyses of their genetic characteristics. A variety of molecular techniques have been described for Borrelia isolate speciation, molecular epidemiology, and pathogenicity studies. In this unit, we focus on three basic protocols, PCR‐RFLP‐based typing of the rrs‐rrlA and rrfA‐rrlB ribosomal spacer, ospC typing, and MLST. These protocols can be employed alone or in combination for characterization of B. burgdorferi isolates or directly on uncultivated organisms in ticks, mammalian host reservoirs, and human clinical specimens. Curr. Protoc. Microbiol . 34:12C.1‐12C.31. © 2014 by John Wiley & Sons, Inc.